Isolation of a new bioactive cinnamic acid derivative from the whole plant of Viola betonicifolia. (1st October 2013) - Muhammad, Naveed; Saeed, Muhammad; Adhikari, Achyut; Khan, Khalid Muhammad; Khan, Haroon
Abstract : A new cinnamic acid derivative was isolated from the whole plant of Viola betonicifolia as off white needle. On the basis of various modern spectroscopic techniques including HREI–MS and 1D and 2D NMR, its structure was elucidated as 2, 4-dihydroxy, 5-methoxy-cinnamic acid. It showed marked inhibition against DPPH (diphenyl-2-picryl hydrazyl) free radicals with IC50 = 124 ± 5.76 µM. The antioxidant property of the compound was compared with α-tocopherole and vitamin C having IC50 values 96 ± 0.46 and 90 ± 0.56 µM, respectively. In case of antiglycation assay, the compound exhibited moderate activity (IC50 = 355 ± 7.56 µM) similar to standard compound, rutin (IC50 = 294 ± 0.56 µM). However, it was non-toxic to PC-3 cell line. It is concluded that 2, 4-dihydroxy, 5-methoxy-cinnamic acid has antiglycation potential which was further augmented by its antioxidant activity and thus offered an ideal natural therapeutic option for the effective management of diabetes.